Bleeding Risk under Oral Factor Xa Inhibitors: Meta-analysis of the randomized comparison with Vitamin K Antagonists and Meta-Regression analysis - Nabila Ferahta; Lukshe Kanagaratnam; Moustapha Dramé; Thomas Vogel; Pierre-Jacques Ambrosi; Pierre-Olivier Lang (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
Background: Randomized trials have shown that oral direct factor Xa inhibitors (ODIXa) offer potential advantages over vitamin K antagonists (VKAs). It is however unclear whether the magnitude of their benefi t is similar at the current recommended doses. Objective: We assessed bleeding risks and total mortality associated with ODIXa therapy compared to VKAs among patients with non-valvular atrial fi brillation or acute venous thromboembolic disease. Methods: Medline, Embase and Cochrane library databases were searched to identify all randomized controlled trials comparing ODIXa to VKAs. The main outcomes were major bleeding, major and clinically relevant non-major (CRNM) bleeding, intracranial haemorrhage, gastrointestinal bleeding, total bleeding events and overall mortality. Pooled odds ratios were calculated with random effect model.Metaregression was performed. Results: The use of ODIXa was associated with a signifi cant reduced-risk of major bleeding (OR, 0.72; 95% CI, 0.60-0.87), major and CNRM bleeding (OR, 0.72; 95% CI, 0.54-0.96), intracranial bleeding (OR, 0.48; 95% CI, 0.39-0.59) and total bleeding events (OR, 0.69; 95% CI, 0.60-0.80). No difference in risk of gastrointestinal bleeding was observed in NVAF. A linear association was found between a higher CHADS2 and risk of major bleeding; increasing age and a high quality of warfarin monitoring (TTR) were also correlated with a higher risk of gastrointestinal bleeding on ODIXa. Conclusions: ODIXa therapy was associated with a lower rate of bleedings complications and overall mortality. The gastrointestinal bleeding risk, which was globally similar, was however increasing in ODIXa groups with advancing age and greater quality of VKAs management.